A comparative study of the Early Pleistocene carnivore guild from Dmanisi (Georgia). Issue 162 (January 2022) - Bartolini-Lucenti, Saverio; Madurell-Malapeira, Joan; Martínez-Navarro, Bienvenido; Cirilli, Omar; Pandolfi, Luca; Rook, Lorenzo; Bushkhianidze, Maia; Lordkipanidze, David
Abstract: The carnivore guild of the Early Pleistocene site of Dmanisi is among the most diverse of the Early Pleistocene of the entire Old World. It includes 14 carnivoran taxa: Homotherium latidens, Megantereon whitei, Panthera onca georgica, Acinonyx pardinensis, Lynx issiodorensis ; Pachycrocuta brevirostris ; Canis ( Xenocyon ) lycaonoides, Canis borjgali, Vulpes alopecoides ; Ursus etruscus ; Lutra sp., Martes sp ., Meles sp., and Pannonictis sp. The analysis of this rich carnivore guild was carried out under different methodological approaches to compare the assemblage with other chronological coeval European, Asian, and African sites from a paleobiological perspective. To achieve the goal, we used a permutational hierarchical method called boostrapping cluster analysis based on taxonomic absence/presence matrices (at both generic and specific level) and on ecological matrices (considering dietary preferences/hunting strategies of each carnivoran) and carried out Mantels tests assessing magnitude of time, space, ecology, and taxonomy as source of difference between guilds. Our results suggest a close similarity among the Dmanisi carnivore assemblage and other guilds recorded from European late Villafranchian sites such as Pirro Nord, Venta Micena, and Apollonia 1 and, in a lesser extent, to European Epivillafranchian sites as Vallonnet, Untermassfeld, or the Vallparadís Section. Early to Middle Pleistocene Asian carnivore assemblages display several similarities with the Dmanisi guild mainly in the record and diversity of felid and the canid ecomorphotypes. Eastern African sites such as Olduvai and Omo, as well as South African sites, display a lower similarity with the studied sample, basically for the most diverse hyenid taphocoenoses. To sum up, the present study suggests a close similarity between the Dmanisi carnivore guild and other European Late Early Pleistocene assemblages without close parallels with African or Asian assemblages.